EMR-linked GWAS study: investigation of variation landscape of loci for body mass index in children - Namjou, Bahram; Keddache, Mehdi; marsolo, keith; wagner, michael; lingren, todd; Cobb, Beth; perry, cassandra; kennebeck, stephanie; Holm, Ingrid A.; Li, Rongling; Crimmins, Nancy A.; Martin, Lisa; et al. (Frontiers in Genetics, 2013)
Common variation at the loci harboring the fat mass and obesity gene (FTO), MC4R and TMEM18 are consistently reported as being associated with obesity and body mass index especially in adult population. In order to confirm this effect in pediatric population five European ancestry cohorts from pediatric eMERGE-II network (CCHMC-BCH) were evaluated. Method: Data on 5049 samples of European ancestry were obtained from the Electronic Medical Records (EMRs) of two large academic centers in five different genotyped cohorts. For all available samples, gender, age, height and weight were collected and Body Mass Index (BMI) was calculated. To account for age and sex differences in BMI, BMI z-scores were generated using 2000 Centers of Disease Control and Prevention (CDC) growth charts. A Genome-wide association study (GWAS) was performed with BMI z-score. After removing missing data and outliers based on principal components (PC) analyses, 2860 samples were used for the GWAS study. The association between each SNP and BMI was tested using linear regression adjusting for age, gender, and PC by cohort. The effects of SNPs were modeled assuming additive, recessive and dominant effects of the minor allele. Meta-analysis was conducted using a weighted z-score approach. Results: The mean age of subjects was 9.8 years (range 2-19). The proportion of male subjects was 56%. In these cohorts, 14% of samples had a BMI≥95% and 28%≥85%. Meta analyses produced a signal at 16q12 genomic region with the best result of p=1.43x10E-07 (p (rec)=7.34E-08) for the single nucleotide polymorphism (SNP) rs8050136 at the first intron of FTO gene (z=5.26) and with no heterogeneity between cohorts (p=0.77). Imputation in this region using dense 1000-Genome and Hapmap CEU samples revealed 71 SNPs with p